A new era for low frequency Galactic center transient monitoring. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Kassim, N. E.; Hyman, S. D.; Intema, H.; Lazio, T. J. W.
Abstract: An upgrade of the low frequency observing system of the VLA developed by NRL and NRAO, called low band (LB), will open a new era of Galactic center (GC) transient monitoring. Our previous searches using the VLA and GMRT have revealed a modest number of radio-selected transients, but have been severely sensitivity and observing time limited. The new LB system, currently accessing the 236--492 MHz frequency range, promises ≥5 × improved sensitivity over the legacy VLA system. The new system is emerging from commissioning in time to catch any enhanced sub-GHz emission from the G2 cloud event, and we review existing limits based on recent observations. We also describe a proposed 24/7 commensal system, called the LOw Band Observatory (LOBO). LOBO offers over 100 VLA GC monitoring hours per year, possibly revealing new transients and helping validate ASTRO2010's anticipation of a new era of transient radio astronomy. A funded LOBO pathfinder called the VLA Low Frequency Ionosphere and Transient Experiment (VLITE) is under development. Finally, we consider the impact of LB and LOBO on our GC monitoring program.